Wheat bran biodegradation by edible Pleurotus fungi – A sustainable perspective for food and feed. (December 2017) - Wanzenböck, Elisa; Apprich, Silvia; Tirpanalan, Özge; Zitz, Ulrike; Kracher, Daniel; Schedle, Karl; Kneifel, Wolfgang
Abstract: Wheat bran, a side product of the milling industry, can serve as valuable food component, feed ingredient or feedstock for biorefineries. However, all these applications bear drawbacks of sensory, physiological and technological challenges. The present study investigates an alternative utilization strategy of wheat bran as substrate for mushroom production and evaluates residual substrates for further sustainable application possibilities. Substrates containing 250 g/kg, 500 g/kg and 980 g/kg of wheat bran were inoculated with spores of Pleurotus eryngii and Pleurotus ostreatus followed by solid-state fermentation. Highest biomass yield, protein content and dry matter were obtained on 980 g/kg of bran when inoculated with Pleurotus eryngii . Beyond that, fermentation also markedly decreased the phytate content, the viscosity and the neutral detergent fiber level in this substrate. Furthermore, the substrate containing 980 g/kg bran displayed a remarkable decrease in neutral detergent fiber. Pleurotus fungi production on wheat bran leads to improved edible mushroom quality compared to commonly used substrates and also offers some innovative application possibilities of the fermented substrate in animal feeding. Highlights: Pleurotus spp. were grown on substrates containing different wheat bran proportions. Highest biological efficiency was obtained in substrates containing 98% wheat bran. Mushrooms grown on substrates containing 98% wheat bran had highest product quality. Fermentation led to decreased fat and phytate contents in residual substrates. Fermentation reduced the viscosity of the substrate, most probably due to fiber degradation.